Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/ecs2.2326
|View full text |Cite
|
Sign up to set email alerts
|

The cooler the better? Indirect effect of spring–summer temperature on fecundity in a capital breeder

Abstract: Female reproductive performance is a central component of ungulate population dynamics, and it can be influenced by individual, social, and environmental factors. Researchers have often assumed direct effects of different predictors on reproduction, yet more complex relationships should be considered when investigating temporal variations in life‐history traits within a broader eco‐evolutionary context. In this study, we explored direct effects of individual, social, and environmental predictors on female repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Male Alpine ibex ( Capra ibex ), for example, reduce daytime feeding activity with increasing temperature (Aublet et al, 2009 ), and Mason et al ( 2014 ) demonstrated a negative effect of higher temperatures on time spent foraging in Alpine chamois ( Rupicapra rupicapra ) independent of time of day. Moreover, reductions in female red deer body condition and thus fecundity have been linked with elevated spring–summer temperatures (Corlatti et al, 2018 ), and red deer calves have been shown to experience reduced growth rates under heat stress (Pérez‐Barbería et al, 2020 ). Such stress responses should be reflected in higher glucocorticoid concentrations with increasing temperature during summer, which might provide an early warning sign for population‐level consequences of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Male Alpine ibex ( Capra ibex ), for example, reduce daytime feeding activity with increasing temperature (Aublet et al, 2009 ), and Mason et al ( 2014 ) demonstrated a negative effect of higher temperatures on time spent foraging in Alpine chamois ( Rupicapra rupicapra ) independent of time of day. Moreover, reductions in female red deer body condition and thus fecundity have been linked with elevated spring–summer temperatures (Corlatti et al, 2018 ), and red deer calves have been shown to experience reduced growth rates under heat stress (Pérez‐Barbería et al, 2020 ). Such stress responses should be reflected in higher glucocorticoid concentrations with increasing temperature during summer, which might provide an early warning sign for population‐level consequences of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change patterns may vary between geographical regions in terms of snow and rain (Parmesan and Matthews 2006), with a global increase of temperatures (Hegerl et al 2018), sometimes even having locally contrasting effects on population dynamics of mountain ungulates (Loison et al 1999), thus making it difficult to predict a general pattern. In spite of local variations, it has been suggested that warmer weather during the vegetative season may have particularly negative effects on body mass (Rughetti and Festa-Bianchet 2012;Mason et al 2014a), fecundity of females (Corlatti et al 2018) and offspring survival (Douhard et al 2018;Ferretti et al 2018), affecting population dynamics of mountain herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…In our study area, birth rate was positively influenced by spring-summer precipitation in the previous year, but not in the same year (see methods); this suggests an indirect effect of spring-summer weather on birth rate through improved maternal conditions (cf. Chirichella et al, 2021; see also Corlatti et al, 2018 for red deer).…”
Section: Discussionmentioning
confidence: 99%